Boundary detection capability and influencing factors of electromagnetic resistivity while using drilling tools in a horizontal well - Tian, Yuanshi; Zhu, Jun; Die, Yong; Liu, Limeng; Yue, Can; Wang, Xuanguang; Zhu, Yusha (Frontiers in Earth Science, 2023)
With the increase of mining scale of horizontal wells and highly deviated wells, electromagnetic boundary detection LWD technology plays an important role in boundary detection. This paper studies on three types of antenna structures commonly used in electromagnetic boundary detection technology and the measurement methods as well as carries out numerical simulation of the edge detection ability of the three structures in horizontal wells. The simulation experiment analyzes the influence of formation resistivity contrast, frequency, spacing and other factors on the edge detection ability, and provides data support for the design of instrument antenna parameters.